2017
DOI: 10.7717/peerj.3672
|View full text |Cite
|
Sign up to set email alerts
|

Presence of the tunicate Asterocarpa humilis on ship hulls and aquaculture facilities in the coast of the Biobío Region, south central Chile

Abstract: Non-native ascidians are important members of the fouling community associated with artificial substrata and man-made structures. Being efficient fouling species, they are easily spread by human-mediated transports (e.g., with aquaculture trade and maritime transports). This is exemplified by the ascidian Asterocarpa humilis which displays a wide distribution in the Southern Hemisphere and has been recently reported in the Northern Hemisphere (NW Europe). In continental Chile, its first report dates back from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The presence of A. humilis has been reported in the Southern Hemisphere in both, artificial (Kesteven 1909;Clarke and Castilla 2000;Monniot et al 2001;Schwindt et al 2014;Turon et al 2016b;Page and Kelly 2016;Pinochet et al 2017;this study) and natural habitats (Varela 2007;Page and Kelly 2016; this study). In the Northern Hemisphere, the species is introduced and has been mainly found in harbors (Bishop et al 2013;Kenworthy et al 2018).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…The presence of A. humilis has been reported in the Southern Hemisphere in both, artificial (Kesteven 1909;Clarke and Castilla 2000;Monniot et al 2001;Schwindt et al 2014;Turon et al 2016b;Page and Kelly 2016;Pinochet et al 2017;this study) and natural habitats (Varela 2007;Page and Kelly 2016; this study). In the Northern Hemisphere, the species is introduced and has been mainly found in harbors (Bishop et al 2013;Kenworthy et al 2018).…”
Section: Discussionsupporting
confidence: 56%
“…Monniot and Monniot (1983) reported the presence of C. robinsoni in the Magellanic region of Argentina (Franklin Bay), in a presumably natural habitat (F. Monniot personal communication, specimens attached to Pyura legumen from MNHN collection S1 CNE 09). In the SE Pacific, we report for the first time the presence of A. humilis in natural habitats (Table 1), while all the previous records corresponded to artificial settings (Clarke and Castilla 2000;Manríquez et al 2014;Turon et al 2016a, b;Pinochet et al 2017;Leclerc et al 2018).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…For example, a study carried out in the ballast water and hulls of 186 vessels in the North Sea found that 57% of the species recorded were non-native (Gollasch, 2002). Similar studies conducted in the coast of Chile revealed the presence of the invasive ascidian Asterocarpa humilis attached to hulls of international ships, which may explain the rapid spread of this species for more than 2,000 km along the coast (Pinochet et al, 2017).…”
Section: Discussionmentioning
confidence: 76%